Os processos de (re)estruturação do tecido urbano de Vila Rica: a influência da Igreja Católica - Rafael Palhares Machado (2011)
Since the beginning of formation of Ouro Preto (formerly Vila Rica), the Church stood out in the landscape of the camps wich were created there. Simultaneously, the streets (and churchyards / plazas) were then setting, often from the surroundings of these temples. In the first decade of thecentury, two parishes (known as Nossa Senhora doPilar de Ouro Preto and Nossa Senhora da Conceição de Antonio Dias) would be formed, containing the small primary nuclei. These ones, assuming a more "permanent" shape, appeared scattered in the landscape, but were quickly joined by paths to integrate a single village. This research presents a reading of the formation and evolution of these primitive nuclei, emphasizing the relative importance of the participation of Christian culture in the definition of intra-urban spaces. At first, elements of a religious nature were able to foster or, at least, induce the formation of primary nuclei or camp, as they were known. In subsequent steps - gradually - the temples (chapels), accommodated in pre-consolidation regions, not only influenced socially, but also contributed, many times, for ordering and even the emergence of new camps. In order to shed light on the spatiality defined by the Catholic Church in the mining area, thechoice of Villa Rica was due to the fact of having hosted the Captaincy of Minas and, therefore, its importance/ uniqueness as a large and complex Portuguese Americas eighteenth-century urban center. As a time window, we took as basis the original tissue formation, which occurred inthe late seventeenth century and throughout the eighteenth century. Although our focus has been the performance of buildings of a religious nature (churches and chapels) in the constitution of the urban fabric of Villa Rica, we also consider other relevant factors that both contributed to define the conformation of that space, ruling the logic of its output, form and ownership.